Kombinasi RSA-CRT dengan Random LSB untuk Keamanan Data di Kanwil Kementerian Agama Prov. Sumatera Utara - Niti Ravika Nasution (Program Studi Sistem Informasi, 2017)
In this study the authors use Cryptographic Algorithms Rivest Shamir Adleman Chinese Remainder Theorem (RSA-CRT) and steganography technique Random Least Significant Bits (LSB). RSA-CRT is basically the same as usual, but utilizing RSA CRT theorem to shorten the bit size decryption exponent d by hiding d on congruent systems that accelerate time decryption, the difference in the key generation process and the decryption process. Cryptographic algorithm RSA-CRT produce ciphertext stored into a picture (image) using Steganography technique Random Least Significant Bits (LSB). The workings of Random LSB is storing the message (ciphertext) in the first bit or the second bit random key for use random number generator Pseudo Random Number Generator (PRNG) with Linear Congruential Generator (LCG) method. Ciphertext stored in a picture (image) has extracted key re-use random number generator at the time of inserting the message. Then the ciphertext is decrypted back by the algorithm RSA-CRT to produce the original text (plaintext). Merging Cryptographic Algorithm RSA-CRT with Steganography Technique Simple LSB than with Random LSB generate higher PSNR and MSE is lower, which means better level of data security and more resistant to attack. Has more difficult to find a secret message by cryptanalysis and steganalyst.